2017
DOI: 10.1186/s12877-017-0580-7
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study on living arrangements of older men and women and risk for basic activities of daily living disability: findings from the AGES project

Abstract: BackgroundLiving arrangements of older adults have changed worldwide with increasing solitary and non-spouse households, which could affect social care systems. However, the relationship between these households and disability onset has remained unclear. We examined the relationship between living arrangements and the onset of basic activities of daily living disability in older adults, with a focus on gender differences and cohabitation status of those without a spouse.MethodsData from 6600 men and 6868 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
4
40
0
2
Order By: Relevance
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
“…In other studies, functional decline was assessed by means of access to public long‐term care services 37,41,60,63,64,67,68,71,81,87,88 . One study considered functional decline by means of years with active life 62 whilst in another study, a functional decline measurement was not described 59 (On‐line Appendix [Outcome Definition]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,31,32 In addition, our findings showed a gender difference, with a stronger association between marriage and mortality in men than women in both countries. Other studies have found similar gender differences, 28 suggesting that husbands rely more on social support exchange with their wives, 33 who also take a larger role in controlling their husbands' health-related behaviors. 34 In particular, our additional analysis found a significantly higher risk in divorced men as compared to married men in both countries.…”
Section: Discussionmentioning
confidence: 81%